2015
DOI: 10.1007/s00221-015-4425-3
|View full text |Cite
|
Sign up to set email alerts
|

Position shifts of fMRI-based population receptive fields in human visual cortex induced by Ponzo illusion

Abstract: Ponzo illusion is a well-known perceptual phenomenon in which the perceived sizes of visual objects are altered by visual depth cues created by converging lines at the horizon. One possible neural mechanism of the Ponzo illusion is the receptive field position shifts of V1 neurons, as supported by a recent monkey electrophysiological study (Ni et al. in Curr Biol 24(14):1653-1658, 2014). Here, we used fMRI-based population receptive field (pRF) mapping technique in combination of psychophysics to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 20 publications
5
38
1
Order By: Relevance
“…This indicates that their neuronal size constancy, relative to perception, was somewhere between 20/35 ¼ 60% and 20/20 ¼ 100%. More recently, He et al (2015) found relatively low, but comparable effects for perception (6.3%) and for V1 population receptive fields (6.8%). Ni et al (2014) also investigated the Ponzo illusion, but looked at a corresponding shift of receptive fields in area V1 of macaque monkeys.…”
Section: Neural Correlates Of Size Constancymentioning
confidence: 88%
See 4 more Smart Citations
“…This indicates that their neuronal size constancy, relative to perception, was somewhere between 20/35 ¼ 60% and 20/20 ¼ 100%. More recently, He et al (2015) found relatively low, but comparable effects for perception (6.3%) and for V1 population receptive fields (6.8%). Ni et al (2014) also investigated the Ponzo illusion, but looked at a corresponding shift of receptive fields in area V1 of macaque monkeys.…”
Section: Neural Correlates Of Size Constancymentioning
confidence: 88%
“…In general, the Ponzo illusion leads to striking effects on size constancy, but the corrections observed are typically less than 100% (Murray et al, 2006;Ni et al, 2014;He et al, 2015). This may be partly due to the use of monocular as opposed to stereo cues to depth.…”
Section: Neural Correlates Of Size Constancymentioning
confidence: 99%
See 3 more Smart Citations